METAMORPHOSIS: REFLECTIONS ON THE THOUGHTS OF IGNACIO ASSIS SILVA OR TRYING TO GET THE HANG OF IT… - Nascimento, Edna Maria Fernandes dos Santos (Laboratório Editorial FCL-UNESP, 2011)
This text, homage to Ignacio Assis Silva, looks for the founding theoretical conceptions of his thoughts. When I looked at his texts, from the 70’s to the 90’s, my reading went through the path of an author who is always worried about revealing the birthplace of meaning. To catch this unique moment of semiosis, Silva proposes the concept of metamorphosis, a key-term which allows us to unite the two ends of his formation: Historical Grammar and Semiotic.